Youth-Led Participatory Video as a Strategy to Enhance Inuit Youth Adaptive Capacities for Dealing with Climate Change - MacDonald, Joanna Petrasek; Ford, James; Willox, Ashlee Cunsolo; Mitchell, Claudia; Productions, Konek; Media Lab, My Word Storytelling and Digital; Community Government, Rigolet Inuit (ARCTIC, 2015)
Rapid climatic and environmental changes experienced throughout the Canadian North are having significant impacts on the lives of Inuit, with implications for the future of the large Inuit youth population. Within the adaptation research and practitioner community, youth voices, perspectives, and involvement are essential in ensuring representative and sustainable adaptation strategies. This paper examines the potential of youth-led participatory video (PV) as a strategy to foster known protective factors that underpin the resilience of youth and their capacity to adapt to various stresses, including impacts of climate change. The work draws on a case study from the Inuit community of Rigolet, Nunatsiavut, Labrador, Canada, where a two-week PV workshop was conducted with seven youth and followed by in-depth interviews with participants and community members. The findings show that PV may be a pathway to greater adaptive capacities because the process connects to known protective factors that enhance resilience of circumpolar indigenous youth. PV also shows promise as a strategy to engage youth in sharing insights and knowledge, connect generations, and involve young Inuit in planning and decision making in general. Les changements climatiques et environnementaux rapides qui surviennent dans le Nord canadien ont des répercussions importantes sur la vie des Inuits, avec des conséquences pour l’avenir de la grande population de jeunes Inuits. Au sein de la communauté de praticiens et de recherche sur l’adaptation, la voix des jeunes, leurs perspectives et leur participation sont essentielles pour assurer la mise en oeuvre de stratégies d’adaptation représentatives et durables. Cet article examine la possibilité de faire des vidéos participatives dirigées par les jeunes comme stratégie pour favoriser les facteurs de protection connus qui sous-tendent la résilience chez les jeunes et leur capacité d’adaptation face à divers agents stressants, notamment les conséquences du changement climatique. Le document ...